Nightpool - Murphy, Shirley Rousseau (Harper & Row, 1985)
Injured in battle with the Dark Raiders, sixteen-year-old Tebriel is healed by a colony of talking otters and sets out to fight the Dark and its forces of evil in the world of Tirror.